Container Transshipment and Logistics in the Context of Urban Economic Development. (10th November 2015) - Slack, Brian; Gouvernal, Elisabeth
Abstract: It is widely recognised that there are strong relationships between containerisation and supply chains that are giving rise to significant clusters of logistics firms around the large gateway ports, which helps reinforce the status of many as global cities. Recent research, policy documents and regional development strategies suggest that transshipment hubs should be able to develop logistics businesses as well. In this paper, it is argued that the differences between gateway ports and transshipment hubs are very great, and that while the shipping lines have been eager to establish transshipment in many locations, logistics firms are reluctant to follow. A number of reasons for this to be the case are examined, including the long‐term uncertainty of shipping services to transshipment hubs, the costs of stripping containers in hub ports with no scale advantages, the distance from major markets, and the limited volume of actual goods available in most hubs. Empirical evidence is presented to demonstrate the weakness of hubs as logistics centres, the major exception being Singapore. The evidence presented suggests that the economic development potential for cities developing as transshipment hubs is much more limited than suggested in the literature.